2018
DOI: 10.18535/jmscr/v6i6.110
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Morphometric Study of Branching Pattern of M2 Segment of Middle Cerebral Artery in Human Cadaveric Brains

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Pattern 3 or bifurcation (97.8%) was the most common, followed by trifurcation (1.04%), early bifurcation (0.51%) and single trunk (0.17%). The duplicated MCA and fenestration were seen in 0.34% and 0.17%, respectively.The incidence of bifurcation in the present study is comparable to that in the study byKadam et al (2018). The incidence of bifurcation was higher in males (97.8%) as compared to females (91.7%) in our study.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Pattern 3 or bifurcation (97.8%) was the most common, followed by trifurcation (1.04%), early bifurcation (0.51%) and single trunk (0.17%). The duplicated MCA and fenestration were seen in 0.34% and 0.17%, respectively.The incidence of bifurcation in the present study is comparable to that in the study byKadam et al (2018). The incidence of bifurcation was higher in males (97.8%) as compared to females (91.7%) in our study.…”
supporting
confidence: 83%
“…The bifurcation is the most common branching pattern of MCA with minimum and maximum incidence in cadaveric studies reported to be 48% and 96.5% (Kadam et al, 2018;Reci, 2019), respectively. In cadavers from India, incidence varies from 64.7%-96.5% (Kadam et al, 2018;Gunnal et al, 2019). The bifurcation is seen in 73% to 92.7% in imaging studies (Sadatamo et al, 2013;Vuillier et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation